Microbiome analysis among bats describes influences of host phylogeny, life history, physiology and geography - PHILLIPS, CALEB D.; PHELAN, GEORGINA; DOWD, SCOT E.; McDONOUGH, MOLLY M.; FERGUSON, ADAM W.; DELTON HANSON, J.; SILES, LIZETTE; ORDÓÑEZ-GARZA, NICTÉ; SAN FRANCISCO, MICHAEL; BAKER, ROBERT J. (Molecular ecology, 2012)
Metagenomic methods provide an experimental approach to inform the relationships between hosts and their microbial inhabitants. Previous studies have provided the conceptual realization that microbiomes are dynamic among hosts and the intimacy of relation between micro‐ and macroorganisms. Here, we present an intestinal microflora community analysis for members of the order Chiroptera and investigate the relative influence of variables in shaping observed microbiome relationships. The variables ranged from those considered to have ancient and long‐term influences (host phylogeny and life history) to the relatively transient variable of host reproductive condition. In addition, collection locality data, representing the geographic variable, were included in analyses. Results indicate a complex influence of variables in shaping sample relationships in which signal for host phylogeny is recovered at broad taxonomic levels (family), whereas intrafamilial analyses disclosed various degrees of resolution for the remaining variables. Although cumulative probabilities of assignment indicated both reproductive condition and geography influenced relationships, comparison of ecological measures among groups revealed statistical differences between most variable classifications. For example, ranked ecological diversity was associated with host phylogeny (deeper coalescences among families were associated with more microfloral diversity), dietary strategy (herbivory generally retained higher diversity than carnivory) and reproductive condition (reproductively active females displayed more diverse microflora than nonreproductive conditions). Overall, the results of this study describe a complex process shaping microflora communities of wildlife species as well as provide avenues for future research that will further inform the nature of symbiosis between microflora communities and hosts.